CREEP FAILURE ANALYSIS OF THERMAL RECOVERY WELLHEAD - CAO XuXiang; YAN TingJun; WANG TingYi; LI Feng (Jixie qiangdu)
In view of the creep failure of the thermal recovery wellhead under the conditions of steam flood and steam stimulation,the creep test of 30CrMo at 390℃ and four different stresses was carried out. The test results were fitted and the parameters of the combined time hardening model were obtained.It is verified by short-term experiments that the error between the calculated value of the combined time hardening model and the test value is less than 15%.Using ANSYS Workbench,the creep failure process of the main pressure parts of the thermal recovery wellhead under constant temperature and load condition and intermittent load condition are simulated,and the failure time of the main pressure parts under two conditions is obtained,which is of great significance to the service life evaluation of the thermal recovery wellhead.